An investigation of the interlayer adhesion strength between the granular base and lightly cemented subbase and its influence on the pavement performance - Ntirenganya, Naphtal (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2015.